2013
DOI: 10.1108/09526861311288596
|View full text |Cite
|
Sign up to set email alerts
|

Data recording aids in acute admissions

Abstract: This audit shows that in an acute setting, over one-quarter of clinical admission data were not captured and devices aimed at improving data capture had no demonstrable effect. The authors suggest that in current hospital practice, focussed clinical training is more likely to improve patient admission records than employing recording aids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Komponen proses terutama pada penanganan pasien yang bisa terkendala seperti alat yang kurang memadai, tempat tunggu yang kurang nyaman, tidak kondusifnya lingkungan rumah sakit dapat berakibat pada penilaian pasien terhadap layanan kesehatan, yang dapat mempengaruhi kunjungan selanjutnya (Milella et al, 2021). Hal ini juga didukung dalam penelitian bahwa proses berpengaruh signifikan terhadap kepuasan pelanggan (Chimwaza et al, 2012) Elemen kelima people, Rumah Sakit salah satu faktor penting adalah Sumber Daya Manusia yang juga berperan penting dalam suksesnya Rumah sakit tersebut (Williams et al, 2013). Kepuasan pasien sangat dipengaruhi oleh penyedia layanan sehingga manajemen Rumah sakit akan mempertimbangkan untuk merekrut tenaga medis dan administrasi yang sesuai dengan jabatannya, selain kemampuan hardskill juga diperlukan kemampuan soft skill seperti keramahan, kesungguhan dalam melayani, komunikasi yang baik dan sopan yang semua itu bertujuan untuk meningkatkan kepuasan pasien sehingga mempengaruhi pilihan dalam kunjungan rumah sakit Kembali (Bao et al, 2013).…”
Section: Pembahasanunclassified
“…Komponen proses terutama pada penanganan pasien yang bisa terkendala seperti alat yang kurang memadai, tempat tunggu yang kurang nyaman, tidak kondusifnya lingkungan rumah sakit dapat berakibat pada penilaian pasien terhadap layanan kesehatan, yang dapat mempengaruhi kunjungan selanjutnya (Milella et al, 2021). Hal ini juga didukung dalam penelitian bahwa proses berpengaruh signifikan terhadap kepuasan pelanggan (Chimwaza et al, 2012) Elemen kelima people, Rumah Sakit salah satu faktor penting adalah Sumber Daya Manusia yang juga berperan penting dalam suksesnya Rumah sakit tersebut (Williams et al, 2013). Kepuasan pasien sangat dipengaruhi oleh penyedia layanan sehingga manajemen Rumah sakit akan mempertimbangkan untuk merekrut tenaga medis dan administrasi yang sesuai dengan jabatannya, selain kemampuan hardskill juga diperlukan kemampuan soft skill seperti keramahan, kesungguhan dalam melayani, komunikasi yang baik dan sopan yang semua itu bertujuan untuk meningkatkan kepuasan pasien sehingga mempengaruhi pilihan dalam kunjungan rumah sakit Kembali (Bao et al, 2013).…”
Section: Pembahasanunclassified
“…This review showed that the use of a pro forma improves the quality of clerking documentation in elective surgical patients, and that standardisation of the medical record improved the quality of patient care. [6][7][8][9][10][11][12][13][14][15] Evidence is presented across the audits that the use of a pro forma leads to significantly improved documentation for surgical patients, in areas such as previous medical history and medication history. [7,12,13,15] It has also been shown to significantly improve the completion of VTE assessment.…”
Section: Designmentioning
confidence: 99%
“…[14] After seeing the improvement that the introduction of the pro forma had on documentation for patients admitted directly to the ward, we wanted to look more widely at all vascular surgery patients admitted to the hospital. Those that are admitted via A&E are typically clerked either on the computerised records system or using history sheets.…”
Section: Strategymentioning
confidence: 99%
“…However, these efforts are prone to abandonment when local champions of their use move on (26) and it is recognized that the usage of proformas often tails off over time for a variety of reasons (e.g. logistical issues with re-printing when initial supplies are depleted) (27). Use of pre-printed stickers for consent may also pose a medico-legal issue given the implications of recent Supreme Court judgements, who found in Montgomery vs Lanarkshire Health Board that pre-procedure risk documentation should not only be generic but also reviewed for significance to the individual patient (28).…”
Section: Introductionmentioning
confidence: 99%